2014
DOI: 10.1038/cgt.2014.28
|View full text |Cite
|
Sign up to set email alerts
|

Role of MAPK in oncolytic herpes viral therapy in triple-negative breast cancer

Abstract: Triple-negative breast cancers (TNBCs) have poor clinical outcomes owing to a lack of targeted therapies. Activation of the MEK/MAPK pathway in TNBC has been associated with resistance to conventional chemotherapy and biologic agents and has a significant role in poor clinical outcomes. NV1066, a replication-competent herpes virus, infected, replicated in and killed all TNBC cell lines (MDA-MB-231, HCC1806, HCC38, HCC1937, HCC1143) tested. Greater than 90% cell kill was achieved in more-sensitive lines (MDA-MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Here, we demonstrate that the combination of T-VEC and MEK inhibition increases melanoma tumor cell killing through increased viral replication and apoptosis in vitro and enhances melanomaspecific adaptive immune responses in vivo. Previous reports have described interactions between MAPK pathway inhibition and other oncolytic viruses (12,19). MEK inhibition was found to increase oncolytic adenovirus replication and tumor cell killing, possibly through up-regulation of coxsackievirus and adenovirus receptor (20).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Here, we demonstrate that the combination of T-VEC and MEK inhibition increases melanoma tumor cell killing through increased viral replication and apoptosis in vitro and enhances melanomaspecific adaptive immune responses in vivo. Previous reports have described interactions between MAPK pathway inhibition and other oncolytic viruses (12,19). MEK inhibition was found to increase oncolytic adenovirus replication and tumor cell killing, possibly through up-regulation of coxsackievirus and adenovirus receptor (20).…”
Section: Discussionmentioning
confidence: 84%
“…Although these findings await further clinical validation, the potential for combining MAPK inhibition with immunotherapy is particularly appealing because MAPK inhibitors act directly on mutated tumor cells, resulting in release of soluble tumor-associated antigens, whereas immunotherapy acts on immune cells to promote innate and adaptive immune responses and/or prevent suppression of host antitumor immunity (11). Preclinical studies have suggested improvements in therapeutic antitumor activity between oncolytic viruses and MEK inhibition in a murine breast cancer model (12). The combination of MEK inhibition and oncolytic viruses has not been tested in melanoma and has not yet entered clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Gholamit.et.al demonstrated that oncolytic viral therapies were of great promise, and at present, viral therapy with NV1066 can cause a significant decrease in the p-MEK and p-MAPK (Gholami et al, 2014).…”
Section: Mapk and Breast Cancermentioning
confidence: 99%
“…Previous studies have shown this pathway to be highly prevalent in TN breast cancer as opposed to other breast cancer subtypes (Hoeflich et al 2009; Balko et al 2012; Hashimoto et al 2014), thus supporting our findings. Studies have also shown that activation of MAPK pathway (Eralp et al 2008; Gholami et al 2014; Giltnane and Balko 2014; Hashimoto et al 2014; Qi et al 2015; Loi et al 2016) significantly correlates with tumor proliferation and disease progression in TN tumors. MAPK pathway is a sequentially activated cascade consisting of key genes such as Ras, Raf, MEK, and ERK.…”
Section: Discussionmentioning
confidence: 99%